2016
DOI: 10.1021/acsmedchemlett.6b00388
|View full text |Cite
|
Sign up to set email alerts
|

GluN2A-Selective Pyridopyrimidinone Series of NMDAR Positive Allosteric Modulators with an Improved in Vivo Profile

Abstract: ABSTRACT:The N-methyl-D-aspartate receptor (NMDAR) is an ionotropic glutamate receptor, gated by the endogenous coagonists glutamate and glycine, permeable to Ca 2+ and Na + . NMDAR dysfunction is associated with numerous neurological and psychiatric disorders, including schizophrenia, depression, and Alzheimer's disease. Recently, we have disclosed GNE-0723 (1), a GluN2A subunit-selective and brain-penetrant positive allosteric modulator (PAM) of NMDARs. This work highlights the discovery of a related pyridop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Whether PAMs could affect KET-induced anesthesia is unclear. In the present study, GNE-5729, a recently discovered GluN2A subunit-selective PAM 8 , was shown to dose-dependently reduce ketamine-induced LORR.…”
Section: Discussionsupporting
confidence: 47%
“…Whether PAMs could affect KET-induced anesthesia is unclear. In the present study, GNE-5729, a recently discovered GluN2A subunit-selective PAM 8 , was shown to dose-dependently reduce ketamine-induced LORR.…”
Section: Discussionsupporting
confidence: 47%
“…As for GluN2A-PAMs, scientists are making efforts in obtaining clean molecular profiles due to a PAM binding site shared between NMDARs and AMPA receptors (AMPARs) [54]. Among PAMs, GNE-0723 was the first to be identified with a high potency and brain penetrance but poor pharmacokinetic profile [65,66]. After modification of GNE-0723 structure into GNE-5729, almost fivefold increased selectivity against AMPAR was achieved, maintaining good GluN2A potency and specificity [66].…”
Section: Nmdar Structure: Focus On the Glun2a Subunitmentioning
confidence: 99%
“…Among PAMs, GNE-0723 was the first to be identified with a high potency and brain penetrance but poor pharmacokinetic profile [65,66]. After modification of GNE-0723 structure into GNE-5729, almost fivefold increased selectivity against AMPAR was achieved, maintaining good GluN2A potency and specificity [66]. Overall, even if several advances have been performed in the last decade trying to identify novel compounds that are able to modulate selectively the GluN2A-containing NMDARs, additional work is needed to reach this goal.…”
Section: Nmdar Structure: Focus On the Glun2a Subunitmentioning
confidence: 99%
“…The structure of the human GluN1/GluN2A ligand-binding domain (LBD) was obtained from the Protein Data Bank (ID: 5TP9). The crystal structure of LBD of NMDA was measured by X-ray diffraction with resolution 2.4 Å [ 53 ]. The crystal structure of TrkA was obtained from the Protein Data Bank (ID: 4AOJ), with resolution 2.75 Å measured by X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%